The Influence of Social Comparison on Psychological Distress Among Users Who Engage in Sarcasm on Social Media - Muhammad Nur Hidayat Nurdin; Yusfitri Nursyahwalni Mangarengi; Perdana Kusuma (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
Social media users are increasingly vulnerable to engaging in social comparison with others, a behavior that may contribute significantly to the emergence of psychological distress. In managing the negative emotions that arise from such comparisons, individuals often resort to sarcasm as a coping strategy. This study aims to examine the influence of social comparison on psychological distress among individuals who exhibit sarcastic behavior on social media, with the expectation that the findings will provide valuable insights into this phenomenon. Utilizing a quantitative research method, the study involved 150 respondents aged 18–40 who engage in sarcastic behavior online. The results revealed a statistically significant effect, with a p-value of < 0.001 and a coefficient of determination (R²) of 0.192, indicating that the social comparison variable accounts for 19.2% of the variance in psychological distress. The remaining variance is attributable to other factors not examined in this study. These findings indicate a significant relationship between social comparison and psychological distress among sarcastic social media users. The implications of this study emphasize the importance of educational initiatives to raise awareness about the negative psychological impacts of social comparison in digital environments and underscore the need to foster more adaptive coping strategies to mitigate these risks.